THE PECULIARITIES OF LEONID SOLOVYOV'S NOVEL "THE TALE OF KHODJA NASREDDIN": THE AUTHOR'S VIEW AND FEATURES OF THE NOVEL - Xalikova E. S. (Modern American Journals, 2025)
Analysis of Leonid Solovyov's novel reveals the folkloric nature of the protagonist. This aspect is reflected in the epigraph, which simultaneously points to the deep antiquity of the narrative and its folk, polyphonic character.
Keywords: Locus, topos, space, chronotope, hero, novel, image.